N, N-Disubstituted-N′-acylthioureas as modular ligands for deposition of transition metal sulfides. Issue 8 (7th February 2018) - Ali, Zahra; Richey, Nathaniel E.; Bock, Duane C.; Abboud, Khalil A.; Akhtar, Javeed; Sher, Muhammad; McElwee-White, Lisa
Abstract : Readily available N, N -disubstituted- N ′-acylthiourea complexes are single source precursors for aerosol assisted chemical vapor deposition of metal sulfide thin films. Abstract : First row transition metal complexes (Ni, Co, Cu, Zn) with N, N -disubstituted- N ′-acylthiourea ligands have been synthesized and characterized. Bis( N, N -diisopropyl- N ′-cinnamoylthiourea)nickel was found to have the lowest onset temperature for thermal decomposition. Thin film deposition of Ni, Co, and Zn sulfides by aerosol assisted chemical vapor deposition from their respective N, N -diisopropyl- N ′-cinnamoylthiourea complexes at 350 °C has been demonstrated.